2007
DOI: 10.1055/s-2007-967196
|View full text |Cite
|
Sign up to set email alerts
|

New Dihydrochalcones and Anti-Platelet Aggregation Constituents from the Leaves of Muntingia calabura

Abstract: Two new dihydrochalcones, 2,3-dihydroxy-4,3',4',5'-tetramethoxydihydrochalcone (1) and 4,2',4'-trihydroxy-3'-methoxydihydrochalcone (2), and a new flavanone, (2R,3R)-(-)-3,5-dihydroxy-6,7-dimethoxyflavanone (3), together with nineteen known compounds have been isolated from the leaves of Muntingia calabura. The structures of three new compounds were determined through spectral analyses including extensive 2D-NMR data. Among the isolates, 2,3-dihydroxy-4,3',4',5'-tetramethoxydihydrochalcone, 5,7-dihydroxy-3-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
0
15
0
3
Order By: Relevance
“…This was followed a year later by another report from the same group on the isolation of chalcones and flavonoids from the leaves of M. calabura (Chen et al, 2007), collected from Kaohsiung City, Taiwan, in June 2001. Prior to the isolation processes, the MEMC L was partitioned using H 2 O-CHCl 3 to obtain the water-soluble and CHCl 3 -soluble partitions with the former also further partitioned using H 2 O and n-BuOH to afford an n-BuOH-soluble and H 2 O-soluble fractions.…”
Section: Vernacular Names Country Referencesmentioning
confidence: 93%
See 2 more Smart Citations
“…This was followed a year later by another report from the same group on the isolation of chalcones and flavonoids from the leaves of M. calabura (Chen et al, 2007), collected from Kaohsiung City, Taiwan, in June 2001. Prior to the isolation processes, the MEMC L was partitioned using H 2 O-CHCl 3 to obtain the water-soluble and CHCl 3 -soluble partitions with the former also further partitioned using H 2 O and n-BuOH to afford an n-BuOH-soluble and H 2 O-soluble fractions.…”
Section: Vernacular Names Country Referencesmentioning
confidence: 93%
“…Then 2 years later, upon vigorous phytochemistry studies on the same sample of M. calabura leaves that were collected in Kaohsiung City, Taiwan, in June 2001, Chen et al (2007) again reported on the isolation of 22 compounds from the CHCl 3 -soluble partitions and n-BuOH-soluble fraction prepared from the MEMC L as described earlier (Chen et al, 2005). Of the isolated compounds, three were new compounds [2,3-dihydroxy-4,3 0 ,4 0 ,5 0 -tetramethoxydihydrochalcone (65), 4,2 0 ,4 0 -trihydroxy-3 0 -methoxydihydrochalcone (66), and (2R,3R)-(À)-3,5-dihydroxy-6,7-dimethoxyflavanone (67)], and the others were known compounds [b-sitostenone (41), mixture of b-sitosterol (43) and stigmasterol (68), 7-methoxyflavone (69), 5,7-dihydroxy-3-methoxyflavone (70), 5,7-dihydroxy-6-methoxyflavone (71), 5,4 …”
Section: Vernacular Names Country Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and eleven known compounds(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Berryammone A (1) was isolated as a reddish gum, and the sodium adduct ion [M + Na] + (m/z 283.0948) in HR-ESI-MS was consistent with the formula C15 H 16 O 4 Na.…”
mentioning
confidence: 91%
“…(Tiliaceae) is a large tree, distributed in southern India, Ceylon, Philippines, and Taiwan [1]. The plants of the family Tiliaceae are rich in flavonoids with flavones, flavanones, flavans, and biflavans as the major constituents [2][3][4][5][6][7], some of which have demonstrated cytotoxic [2, 3-5] and antiplatelet aggregation activities [7]. In our studies on constituents of Formosan plants for in vitro inhibitory activity on neutrophil proinflammatory responses, B. ammonilla has been found to be an active species.…”
mentioning
confidence: 99%